2009
DOI: 10.1017/s0022112008004655
|View full text |Cite
|
Sign up to set email alerts
|

Wake structure of a transversely rotating sphere at moderate Reynolds numbers

Abstract: The uniform flow past a sphere undergoing steady rotation about an axis transverse to the free stream flow was investigated numerically. The objective was to reveal the effect of sphere rotation on the characteristics of the vortical wake structure and on the forces exerted on the sphere. This was achieved by solving the time-dependent, incompressible Navier–Stokes equations, using an accurate Fourier–Chebyshev spectral collocation method. Reynolds numbers Re of 100, 250 and 300 were considered, which for a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 25 publications
9
40
1
Order By: Relevance
“…case (e) and case ( f ), the recirculation bubble is evidently mostly suppressed. This near wake is very similar to the 'shear-layer instability' regime reported by Giacobello et al (2009), Kim (2009) and Poon et al (2014) for rigidly mounted rotating spheres at low Reynolds number (Re 1000). They reported single-sided shedding on the advancing side of the rotating sphere.…”
Section: Modes Of Vortex Formationsupporting
confidence: 85%
See 2 more Smart Citations
“…case (e) and case ( f ), the recirculation bubble is evidently mostly suppressed. This near wake is very similar to the 'shear-layer instability' regime reported by Giacobello et al (2009), Kim (2009) and Poon et al (2014) for rigidly mounted rotating spheres at low Reynolds number (Re 1000). They reported single-sided shedding on the advancing side of the rotating sphere.…”
Section: Modes Of Vortex Formationsupporting
confidence: 85%
“…Previous studies (e.g. Giacobello, Ooi & Balachandar 2009;Kim 2009;Poon et al 2014, and references therein) have shown that the onset of the shear-layer instability wake state of a non-oscillating rotating sphere occurs beyond this α value. That wake state forms when fluid that passes the retreating side of the sphere is pushed towards the other side of the wake to form a distinctive one-sided separating shear layer, thus changing the characteristic formation and release of vortex loops that defines the non-rotating wake state.…”
Section: Effect Of Rotation On the Vibration Responsementioning
confidence: 87%
See 1 more Smart Citation
“…The study by Poon et al [17,18] revealed that the orientation of the rotation axis also has a significant effect on the flow structure and hydrodynamic forces. In particular, the shear layer instability mechanism reported by Giacobello et al [11] was found at Re ¼ 300 not only for transverse rotation but also for a limited number of oblique rotation axis angles.…”
Section: Introductionmentioning
confidence: 75%
“…Numerical simulations offer a solution to this problem and by the early 1990s numerical solutions of the governing equations could produce revealing information on the flow field [8]. Subsequent studies solved for the full Navier-Stokes equations using a number of different numerical techniques such as the marker and cell method [9], immersed boundary methods [10] and spectral collocation methods [11][12][13][14][15][16]. The study by Giacobello et al [11] found that rotation significantly altered the structure of the flow field compared with the stationary case, resulting in significant changes in the hydrodynamic forces.…”
Section: Introductionmentioning
confidence: 99%